Preventive behaviour and attitudes towards early childhood caries amongst mothers of toddlers in Bangladesh - Haque, Farzana (United Kingdom, 2025)
Background: Our aim was to analyse mothers of toddlers' preventive behaviour towards ECC in Bangladesh.
Methods: We conducted a cross-sectional survey of mothers and their 6-24-month-old children visiting vaccination centres in Trishal, Bangladesh in 2021. A cluster-sampling method was applied to select 10 immunization centres and all mothers who attended the centres with a 6-24-month-old child were recruited. Mothers' preventive behaviour and attitude towards oral health was determined using a reliable instrument. Clinical examinations were conducted to assess the presence of dental plaque on the labial surfaces of the upper central incisors and the ICDAS II index criteria were utilized to detect ECC. The associations between preventive behaviours and the plaque score and caries status of the children were determined using multivariable logistic regression analysis after adjusting for confounding variables (mother's age and educational status).
Results: The prevalence of ECC among the children was 25.8%. ECC experience was significantly associated with low educational level (p = 0.02) and older age (p = 0.01) of mothers. Of the mothers, 75.2% reported to brush their teeth twice daily and about half of them (48.8%) cleaned their children's teeth daily; and 5.8% with fluoridated toothpaste. The multivariate logistic regression analysis showed that caries preventive behaviour of mothers (AOR = 2.63, 95% CI 1.41-4.91) and the plaque score of the child (AOR = 14.69, 95% CI 7.45-28.9) were significant risk indicators for ECC in the study population.
Conclusions: The prevalence of ECC was high among the Bangladeshi toddlers and factors such as the mothers' preventive behaviour and presence of plaque were associated with the occurrence.